Analysis of Phonological Adaptation of Arabic Loanwords in Yoruba Language - Busari Kehinde Kamorudeen (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study investigates how Arabic loanwords have adapted phonologically into the Yoruba language, driven by historical, religious, and educational exchanges between Arabic and Yoruba speakers. Utilizing qualitative descriptive analysis, the research examines a corpus of loanwords drawn from religious texts, commercial documents, educational resources, and interviews with native Yoruba speakers. Frameworks from generative grammar and phonologically conditioned morphological theory guide the analysis. Findings demonstrate systematic adaptations including phonemic substitutions, syllable restructuring, stress adjustments, and morphological affixation aligning with Yoruba's phonological and grammatical norms. Additionally, semantic shifts such as specialization, broadening, and pejoration reflect deeper sociocultural reinterpretations. These adaptations underscore the dynamic interplay between linguistic borrowing and sociocultural integration, highlighting Arabic loanwords' integral role across religion, education, and commerce in Yoruba-speaking contexts in West Africa. The study contributes to a deeper understanding of cross-linguistic influence and highlights the evolving interplay between phonological structure and sociocultural integration in multilingual West Africa.